2019
DOI: 10.3389/fimmu.2019.00396
|View full text |Cite
|
Sign up to set email alerts
|

Expression of T-Bet, Eomesodermin, and GATA-3 Correlates With Distinct Phenotypes and Functional Properties in Porcine γδ T Cells

Abstract: Unlike mice and humans, porcine γδ T cells represent a prominent subset of T cells in blood and secondary lymphatic organs. GATA-3, T-bet and Eomesodermin (Eomes) are transcription factors with crucial functions in T-cell development and functional differentiation, but their expression has not been investigated in porcine γδ T cells so far. We analyzed the expression of these transcription factors in γδ thymocytes, mature γδ T cells from blood, spleen, lymph nodes, and lung tissue as well as in vitro stimulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 62 publications
5
48
0
Order By: Relevance
“…CD3e was used to identify T cells, and further characterization of total T cells by expression of cell surface markers γδTCR, CD2, CD4, CD8α, and CD27 was assessed. CD2 and CD8α expression are commonly used to identify functional porcine γδ T cell populations (45, 46); CD4 and CD8α expression identify functional porcine αβ T cell populations (47,48); and CD27 expression is indicative of T cell activation and memory states (49)(50)(51)(52). In total, this gating strategy yielded 16 discrete, nonoverlapping IET subpopulations based on CD27 +/expression within each of the 8 defined IET populations ( Fig.…”
Section: Iet Compositions Diverged By Intestinal Location As Pigs Agedmentioning
confidence: 99%
See 1 more Smart Citation
“…CD3e was used to identify T cells, and further characterization of total T cells by expression of cell surface markers γδTCR, CD2, CD4, CD8α, and CD27 was assessed. CD2 and CD8α expression are commonly used to identify functional porcine γδ T cell populations (45, 46); CD4 and CD8α expression identify functional porcine αβ T cell populations (47,48); and CD27 expression is indicative of T cell activation and memory states (49)(50)(51)(52). In total, this gating strategy yielded 16 discrete, nonoverlapping IET subpopulations based on CD27 +/expression within each of the 8 defined IET populations ( Fig.…”
Section: Iet Compositions Diverged By Intestinal Location As Pigs Agedmentioning
confidence: 99%
“…However, differing compositions and abundances of microbial species present in the large intestine compared to the small intestine may play a role in IET activation. Moreover, large intestinal IETs may be exposed to a different repertoire of soluble factors than IETs of the small intestine, such as microbially-derived components including lipopolysaccharide (LPS) or microbially-constructed metabolite products including short-chain fatty acids (SCFAs).In peripheral blood and non-intestinal tissues, the presence or absence of CD8α expression within porcine CD2 + γδ T cells is associated with different functional states.CD2 + CD8α + γδ T cells exhibit greater expression of the effector T cell transcription factor T-bet(52), greater cytokine production (45), and expression patterns of cell surface molecules indicative of T cell activation(29,49) when compared to CD2 + CD8αγδ T cells. Resultingly, CD2 + CD8αγδ T cells are a proposed naïve or memory cell population, while CD2 + CD8α + γδ T cells are proposed to be a terminally differentiated population (45, 52).…”
mentioning
confidence: 99%
“…Pigs are one of the species, including cattle, sheep, and chicken, where γδ T cells represent a substantial proportion of the total T cell population in the blood circulation and secondary lymphoid organs (44,55). When considering the expression of CD2, a positive and negative γδ T cell subset can be identified and it was suggested that these are two different lineages that are already established in the thymus (44,56).…”
Section: Discussionmentioning
confidence: 99%
“…Pigs are one of the species, including cattle, sheep, and chicken, where γδ T cells represent a substantial proportion of the total T cell population in the blood circulation and secondary lymphoid organs (44,55). When considering the expression of CD2, a positive and negative γδ T cell subset can be identified and it was suggested that these are two different lineages that are already established in the thymus (44,56). Based on the role of transcription factors involved in T cell polarization, a recent study addressing the expression of GATA-3 and T-bet in porcine γδ T cells revealed striking differences between the two lineages (44,49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation